A silicon nitride reinforced boron nitride support plate material and a method for preparing the same
Patent Information
- Application Number
- CN202611267908.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-13
AI Technical Summary
非氧化物陶瓷增强相(如SiC)虽然能够有效提升材料的韧性与强度,但其固有的导电性会破坏六方氮化硼优异的绝缘特性;同时,在作为承烧板材料高温服役或烧结过程中,还可能对氮化硅或氮化铝等电子陶瓷的电绝缘性能产生不利影响,从而限制其在高端电子陶瓷基板领域的应用
(1)本发明引入α-氮化硅作为增强相,α-氮化硅具有出色的强度、硬度、耐磨性、优异的高温稳定性及良好的抗热震性能,α-氮化硅作为增强相分布在六方氮化硼基体中,有力地支撑起整体结构,显著提高材料的宏观硬度和耐压强度。同时,α-氮化硅与六方氮化硼的热膨胀系数匹配性良好,有助于降低温度变化过程中产生的热应力集中。在高温烧结过程中,α-氮化硅可发生相变转化形成β-氮化硅,其高长径比的柱状晶体结构能够嵌入并穿插于片状六方h-BN基体中,形成互锁增强结构,从而实现材料的致密化与强韧化协同提升。此外,烧结致密度的提高有助于降低界面热阻,从而在一定程度上改善材料的整体热传导性能。
Smart Images

Figure CN122897690A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of refractory material preparation technology, specifically relating to a silicon nitride reinforced boron nitride sintering plate material and its preparation method. Background Technology
[0002] In recent years, hexagonal boron nitride-based ceramics have been widely used as sintering support materials for electronic ceramics such as aluminum nitride and silicon nitride due to their unique layered crystal structure, extremely low coefficient of thermal expansion, excellent thermal shock stability and creep resistance.
[0003] However, pure hexagonal boron nitride ceramics suffer from low strength, poor density, and sintering difficulties, severely limiting their practical application as substrate materials. To overcome these shortcomings, researchers have attempted to introduce various reinforcing phases, primarily oxide and non-oxide systems. While oxide ceramic additives (such as Al2O3 and ZrO2) can improve material strength to some extent, they may react with hexagonal boron nitride at high temperatures to form low-melting-point borate phases, significantly weakening the material's high-temperature stability and thermal shock resistance. Non-oxide ceramic reinforcing phases (such as SiC) can effectively improve the material's toughness and strength, but their inherent conductivity can compromise the excellent insulating properties of hexagonal boron nitride. Furthermore, during high-temperature service or sintering as substrate materials, they may adversely affect the electrical insulation properties of electronic ceramics such as silicon nitride or aluminum nitride, thus limiting their application in high-end electronic ceramic substrates.
[0004] Therefore, how to achieve synergistic improvement in material densification and mechanical properties while maintaining the excellent insulation and high-temperature stability of hexagonal boron nitride ceramics is a key issue that urgently needs to be addressed in its high-end applications such as firing plates. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a silicon nitride-reinforced boron nitride (HN) sintering plate material and its preparation method. Using α-silicon nitride as the reinforcing phase, a certain amount of α-silicon nitride is composited with lamellar hexagonal boron nitride of different particle sizes. The HN sintering plate material is prepared using a vacuum hot-pressing sintering process. During the high-temperature hot-pressing sintering process, α-silicon nitride transforms into β-silicon nitride, whose high aspect ratio columnar grains can be effectively embedded and intercalated within the lamellar HN matrix, forming an interlocking reinforcement structure. This achieves a synergistic improvement in both densification and toughness of the sintering plate material. Compared with traditional HN sintering plate materials, this invention significantly improves the strength, hardness, thermal conductivity, and thermal shock resistance of the boron nitride sintering plate material, while maintaining excellent electrical insulation properties, making it suitable for the field of high-end electronic ceramic sintering plates.
[0006] The present invention is specifically achieved through the following technical solution: According to the silicon nitride reinforced boron nitride sintering plate material proposed in the present invention, the raw materials include, by weight percentage, 30-69% of plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30-69% of plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 1-10% of silicon nitride with a particle size of 1-10 μm.
[0007] In the aforementioned silicon nitride reinforced boron nitride sintering plate material, the purity of the sheet-like hexagonal boron nitride is ≥99.5%, and the purity of the silicon nitride is ≥99%.
[0008] The aforementioned silicon nitride-reinforced boron nitride sintering plate material uses α-silicon nitride as the silicon nitride.
[0009] The aforementioned silicon nitride reinforced boron nitride sintering plate material is prepared according to the following method: (1) Weigh the raw materials according to the weight percentage. The raw materials include 30-69% of plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30-69% of plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 1-10% of α-silicon nitride with a particle size of 1-10 μm. Put all the raw materials into a ball mill jar for ball milling and mixing. (2) The raw materials after ball milling are placed in an oven to dry, and the dried powder is placed in a ceramic mortar for grinding. Then it is sieved to obtain fine powder after mixing and drying. (3) Press the mixed and dried fine powder into a blank in a stainless steel mold; (4) The pressed blank is placed in a vacuum hot pressing sintering furnace for hot pressing sintering. The sintering pressure is 10-50 MPa, the sintering temperature is 1700-2000 ℃, and the sintering time is 3-5 h. After sintering, it is naturally cooled to room temperature to obtain silicon nitride reinforced boron nitride sintering plate material.
[0010] Preferably, in step (1) ball milling, silicon nitride grinding balls are used, the ball-to-material ratio is 3:1, the grinding medium is anhydrous ethanol, the mass ratio of raw material to anhydrous ethanol is 1:4, the ball mill speed is 100-400 r / min, and the ball milling time is 1-5 h.
[0011] Preferably, the drying temperature in step (2) is 60-100℃, the drying time is 10-24 h, and the ground powder is passed through a 100-mesh sieve to obtain fine powder after mixing and drying.
[0012] Preferably, when pressing the blank in step (3), the pressing rate is 0.1-3 MPa / s, the molding pressure is 50-100 MPa, and the holding time is 10-20 s.
[0013] Preferably, the mold used for vacuum hot pressing sintering in step (4) is a graphite crucible.
[0014] The aforementioned silicon nitride-reinforced boron nitride sintered plate material has a bulk density of 1.70-1.85 g / cm³. 3 It has a room temperature compressive strength of 43-55 MPa, a porosity of 16-20%, a thermal conductivity of 50-60 W / (m·K), and a Vickers hardness of 430-490 HV.
[0015] Compared with the prior art, the present invention has at least the following advantages: (1) This invention introduces α-silicon nitride as a reinforcing phase. α-silicon nitride has excellent strength, hardness, wear resistance, excellent high-temperature stability, and good thermal shock resistance. As a reinforcing phase, α-silicon nitride is distributed in the hexagonal boron nitride matrix, which strongly supports the overall structure and significantly improves the macroscopic hardness and compressive strength of the material. At the same time, the thermal expansion coefficients of α-silicon nitride and hexagonal boron nitride are well matched, which helps to reduce the thermal stress concentration generated during temperature changes. During high-temperature sintering, α-silicon nitride can undergo a phase transformation to form β-silicon nitride. Its columnar crystal structure with a high aspect ratio can be embedded and intercalated in the plate-like hexagonal h-BN matrix to form an interlocking reinforcing structure, thereby achieving a synergistic improvement in the densification and toughness of the material. In addition, the increase in sintering density helps to reduce the interfacial thermal resistance, thereby improving the overall thermal conductivity of the material to a certain extent.
[0016] (2) The silicon nitride reinforced boron nitride sintering plate material of the present invention uses two different particle sizes, micron-sized and nano-sized, of plate-shaped hexagonal boron nitride, plus an appropriate amount of micron-sized α-silicon nitride. This combination of different particle sizes is conducive to achieving a denser particle packing, reducing the internal pores of the material after sintering, thereby increasing the bulk density of the sintering plate material and reducing its porosity.
[0017] (3) The present invention uses a pre-pressing molding process to achieve close packing of loose h-BN and α-silicon nitride powder and effectively remove air between particles to form a dense blank, which is beneficial to densification in the subsequent sintering process, reduces material porosity and increases strength.
[0018] (4) Silicon carbide itself is a semiconductor material. Although using SiC as the reinforcing phase of boron nitride sintering plate can effectively improve the toughness and strength of the material, its inherent conductivity will destroy the excellent insulation properties of hexagonal boron nitride. In contrast, this invention uses α-silicon nitride as the reinforcing phase. Silicon nitride is an excellent electrical insulator. While improving the density and mechanical properties of the boron nitride sintering plate, it will not affect the insulation properties of the boron nitride sintering plate. The process of this invention is simple. It can achieve the synergistic improvement of densification and mechanical properties of boron nitride sintering plate material while maintaining the excellent insulation and high-temperature stability of boron nitride ceramic. It can simultaneously improve its strength, hardness and thermal shock resistance, and effectively optimize the thermal conductivity of the material through densification. Attached Figure Description
[0019] Figure 1 These are SEM images of the α-silicon nitride used in this invention at different magnifications.
[0020] Figure 2 This is a SEM image of the fracture morphology of a pure sheet-like hexagonal boron nitride sintered plate.
[0021] Figure 3 This is a SEM image of the fracture morphology of the silicon nitride-reinforced boron nitride sintered plate prepared in Example 1. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0023] Unless otherwise specified, all conditions in the following embodiments were performed under conventional conditions or conditions recommended by the manufacturer. Raw materials and reagents whose manufacturers are not specified are all commercially available products. Unless otherwise specified, the scientific and technical terminology and experimental methods of this invention are based on the conventional understanding and existing standard methods of those skilled in the art. It should be understood that the parameters such as temperature and holding time involved in this invention are approximate values and are used for illustrative purposes; those skilled in the art can make reasonable adjustments according to actual needs.
[0024] In the following examples, the purity of the plate-shaped hexagonal boron nitride is ≥99.5%, and the purity of the silicon nitride is ≥99%.
[0025] Example 1 A silicon nitride reinforced boron nitride sintering plate material, by weight percentage, comprises 69% flake hexagonal boron nitride with a particle size of 1-10 μm, 30% flake hexagonal boron nitride with a particle size of 20-500 nm, and 1% granular α-silicon nitride with a particle size of 1-10 μm.
[0026] Its preparation method includes the following steps: (1) Raw material mixing: Weigh the raw materials according to the above weight percentages. The raw materials include 69% plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30% plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 1% granular α-silicon nitride with a particle size of 1-10 μm. Put all the raw materials into a ball mill jar, use silicon nitride grinding balls, the ball-to-material ratio is 3:1, and carry out ball milling and mixing in a planetary ball mill. The grinding medium is anhydrous ethanol, the mass ratio of raw materials to anhydrous ethanol is 1:4, the ball mill speed is 300 r / min, and the ball milling time is 2 h. (2) Drying and sieving: The ball-milled raw material is placed in an oven for drying at 80°C for 12 hours; the dried powder is then ground in a ceramic mortar and passed through a 100-mesh sieve to obtain a fine powder after mixing and drying. (3) Pre-pressing: The mixed and dried fine powder is placed in a stainless steel mold and pressed into a blank. The pressure is slowly increased to 30 MPa at a rate of 1 MPa / s, and then held for 15s. (4) Hot pressing sintering: The pressed blank is placed in a graphite crucible, and the graphite crucible is placed in a vacuum hot pressing sintering furnace for hot pressing sintering. The sintering pressure is 20 MPa, the sintering temperature is 1850℃, and the sintering time is 3h. After sintering, it is naturally cooled to room temperature to obtain silicon nitride reinforced boron nitride sintering plate material S1.
[0027] Figure 1 These are SEM images of the α-silicon nitride used in this invention at different magnifications. It can be seen that the α-silicon nitride is formed by the agglomeration of fine granular grains into spherical particles. After being ball-milled and mixed with plate-shaped hexagonal boron nitride, these fine granular grains fill the spaces between the boron nitride plates. During the high-temperature sintering process, they are transformed into columnar β-silicon nitride with a high aspect ratio, which are interspersed in the h-BN plates.
[0028] Figure 2 The image shows the SEM image of the fracture morphology of a pure lamellar hexagonal boron nitride sintered plate. It exhibits a typical layered structure, which is prone to lamellar peeling, causing cracks to propagate along the interlayer, resulting in low material strength and toughness.
[0029] Figure 3This is a SEM image of the fracture morphology of the silicon nitride-reinforced boron nitride (HN) sintered plate prepared in Example 1. It can be observed that needle-like silicon nitride grains are interspersed within the layered HN matrix. These high-strength needle-like grains effectively hinder the single propagation of cracks along the HN interlayers, significantly increasing the crack propagation path and energy consumption through mechanisms such as crack deflection, bridging, and pull-out, thereby fully leveraging the reinforcing and toughening effect of silicon nitride on the HN matrix. Simultaneously, the high-strength silicon nitride interspersed within the HN layers reduces the tendency for surface spalling, enhances the material's wear resistance and thermal shock resistance, and improves upon the shortcomings of insufficient mechanical properties and low density of pure HN sintered plates, meeting the requirements for high-temperature sintered plates under heavy loads and thermal shock environments.
[0030] Example 2 A silicon nitride reinforced boron nitride sintering plate material, by weight percentage, comprises 67% plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30% plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 3% granular α-silicon nitride with a particle size of 1-10 μm.
[0031] Its preparation method includes the following steps: (1) Raw material mixing: Weigh the raw materials according to the above weight percentages. The raw materials include 67% plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30% plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 3% granular α-silicon nitride with a particle size of 1-10 μm. Put all the raw materials into a ball mill jar, use silicon nitride grinding balls, the ball-to-material ratio is 3:1, and carry out ball milling and mixing in a planetary ball mill. The grinding medium is anhydrous ethanol, the mass ratio of raw materials to anhydrous ethanol is 1:4, the ball mill speed is 500 r / min, and the ball milling time is 1.5h. (2) Drying and sieving: The ball-milled raw material is placed in an oven for drying at 100°C for 10 hours; the dried powder is then ground in a ceramic mortar and passed through a 100-mesh sieve to obtain a fine powder after mixing and drying. (3) Pre-pressing: The mixed and dried fine powder is placed in a stainless steel mold and pressed into a blank. The pressure is slowly increased to 50 MPa at a rate of 1 MPa / s, and then held for 15s. (4) Hot pressing sintering: The pressed blank is placed in a graphite crucible, and the graphite crucible is placed in a vacuum hot pressing sintering furnace for hot pressing sintering. The sintering pressure is 30 MPa, the sintering temperature is 1900℃, and the sintering time is 3h. After sintering, it is naturally cooled to room temperature to obtain silicon nitride reinforced boron nitride sintering plate material S2.
[0032] Example 3 A silicon nitride reinforced boron nitride sintering plate material, by weight percentage, comprises 65% flake hexagonal boron nitride with a particle size of 1-10 μm, 30% flake hexagonal boron nitride with a particle size of 20-500 nm, and 5% granular α-silicon nitride with a particle size of 1-10 μm.
[0033] Its preparation method includes the following steps: (1) Raw material mixing: Weigh the raw materials according to the above weight percentages. The raw materials include 65% plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30% plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 5% granular α-silicon nitride with a particle size of 1-10 μm. Put all the raw materials into a ball mill jar, use silicon nitride grinding balls, the ball-to-material ratio is 3:1, and ball milling is carried out in a planetary ball mill. The grinding medium is anhydrous ethanol, the mass ratio of raw materials to anhydrous ethanol is 1:4, the ball mill speed is 400 r / min, and the ball milling time is 2h. (2) Drying and sieving: The ball-milled raw material is placed in an oven for drying at 80°C for 12 hours; the dried powder is then ground in a ceramic mortar and passed through a 100-mesh sieve to obtain a fine powder after mixing and drying. (3) Pre-pressing: The mixed and dried fine powder is placed in a stainless steel mold and pressed into a blank. The pressure is slowly increased to 50 MPa at a rate of 1 MPa / s, and then held for 15s. (4) Hot pressing sintering: The pressed blank is placed in a graphite crucible, and the graphite crucible is placed in a vacuum hot pressing sintering furnace for hot pressing sintering. The sintering pressure is 30 MPa, the sintering temperature is 1850℃, and the sintering time is 3h. After sintering, it is naturally cooled to room temperature to obtain silicon nitride reinforced boron nitride sintering plate material S3.
[0034] Comparative Example 1 A boron nitride sintering plate, by weight percentage, comprises 70% plate-shaped hexagonal boron nitride with a particle size of 1-10 μm and 30% plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, without the addition of silicon nitride.
[0035] The preparation method includes: weighing the raw materials according to the above weight percentages, the raw materials including 70% plate-shaped hexagonal boron nitride with a particle size of 1-10 μm and 30% plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, putting all the raw materials into a ball mill jar, and mixing them in a ball mill. The remaining parameters and operating steps are the same as in Example 1, to obtain boron nitride sintering plate material D1.
[0036] The sintering plate materials obtained in Examples 1-3 and Comparative Example 1 were subjected to performance tests. The bulk density and porosity were measured by Archimedes' displacement method according to the method in the national standard GB / T 2997-2015. The detailed measurement method is a mature existing technology and will not be described in detail here.
[0037] The room temperature compressive strength was tested according to the method in standard GB / T 5072-2008.
[0038] Thermal shock resistance was tested according to the method in standard GB / T 30873-2014.
[0039] The testing methods for thermal conductivity and Vickers hardness are also existing and mature technologies, so they will not be elaborated further.
[0040] The test results are shown in Table 1.
[0041] Table 1 Performance test results of boron nitride sintered plate material As shown in Table 1, compared with Comparative Example 1, Examples 1-3, by adding a certain amount of α-silicon nitride with a particle size of 1-10 μm to the raw materials, significantly improved the bulk density, room temperature compressive strength, thermal shock resistance retention rate, thermal conductivity, and Vickers hardness of the resulting sintering plate materials. α-Silicon nitride possesses excellent strength, hardness, and wear resistance. The introduced α-silicon nitride, distributed as a reinforcing phase within the boron nitride matrix, effectively supports the overall structure, significantly improving the material's macroscopic hardness and compressive strength. Furthermore, the silicon nitride-reinforced boron nitride sintering plate of this invention uses both micron- and nano-sized boron nitride particles, along with an appropriate amount of micron-sized α-silicon nitride. This combination of different particle sizes facilitates denser particle packing, reduces the porosity within the material after sintering, thereby increasing the material's bulk density, reducing interfacial thermal resistance, and improving thermal conductivity to a certain extent. The results in summary indicate that introducing an appropriate amount of α-silicon nitride into the sheet-like hexagonal boron nitride raw material can effectively reduce the porosity of the material and significantly improve the density and comprehensive mechanical properties of the boron nitride sintering plate.
[0042] The above description is merely an embodiment of the present invention and is not intended to limit the present invention in any way. The present invention can also have other embodiments based on the above structure and function, which will not be listed hereafter. Therefore, any simple modifications, equivalent changes, and alterations made by those skilled in the art to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A silicon nitride reinforced boron nitride sintered plate material, characterized in that, By weight percentage, the raw materials include 30-69% plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30-69% plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 1-10% silicon nitride with a particle size of 1-10 μm.
2. The silicon nitride reinforced boron nitride sintering plate material as described in claim 1, characterized in that, The purity of the plate-shaped hexagonal boron nitride is ≥99.5%, and the purity of silicon nitride is ≥99%.
3. The silicon nitride reinforced boron nitride sintering plate material as described in claim 1, characterized in that, The silicon nitride used is α-silicon nitride.
4. The silicon nitride reinforced boron nitride sintering plate material as described in claim 1, characterized in that, Prepared according to the following method: (1) Weigh the raw materials according to the weight percentage. The raw materials include 30-69% of plate-shaped hexagonal boron nitride with a particle size of 1-10 μm, 30-69% of plate-shaped hexagonal boron nitride with a particle size of 20-500 nm, and 1-10% of α-silicon nitride with a particle size of 1-10 μm. Put all the raw materials into a ball mill jar for ball milling and mixing. (2) The raw materials after ball milling are placed in an oven to dry, and the dried powder is placed in a ceramic mortar for grinding. Then it is sieved to obtain fine powder after mixing and drying. (3) Press the mixed and dried fine powder into a blank in a stainless steel mold; (4) The pressed blank is placed in a vacuum hot pressing sintering furnace for hot pressing sintering. The sintering pressure is 10-50 MPa, the sintering temperature is 1700-2000 ℃, and the sintering time is 3-5 h. After sintering, it is naturally cooled to room temperature to obtain silicon nitride reinforced boron nitride sintering plate material.
5. The silicon nitride reinforced boron nitride sintering plate material as described in claim 4, characterized in that, In step (1), when mixing by ball milling, silicon nitride grinding balls are used, the ball-to-material ratio is 3:1, the grinding medium is anhydrous ethanol, the mass ratio of raw material to anhydrous ethanol is 1:4, the ball mill speed is 100-400 r / min, and the ball milling time is 1-5 h.
6. The silicon nitride reinforced boron nitride sintering plate material as described in claim 4, characterized in that, Step (2) The drying temperature is 60-100℃ and the drying time is 10-24 h. The ground powder is passed through a 100-mesh sieve to obtain fine powder after mixing and drying.
7. The silicon nitride reinforced boron nitride sintering plate material as described in claim 4, characterized in that, When pressing the blank in step (3), the pressing rate is 0.1-3 MPa / s, the molding pressure is 50-100 MPa, and the holding time is 10-20s.
8. The silicon nitride reinforced boron nitride sintering plate material as described in claim 4, characterized in that, Step (4) The mold used for vacuum hot pressing sintering is a graphite crucible.
9. The silicon nitride reinforced boron nitride sintering plate material as described in claim 4, characterized in that, The bulk density of the obtained silicon nitride reinforced boron nitride sintered plate material is 1.70-1.85 g / cm³. 3 It has a room temperature compressive strength of 43-55 MPa, a porosity of 16-20%, a thermal conductivity of 50-60 W / (m·K), and a Vickers hardness of 430-490 HV.